The manual orienting response habituation to repeated tactile stimuli in preterm neonates: Discrimination of stimulus locations and interstimulus intervals. Issue 5 (July 2017) - Dumont, Victoria; Bulla, Jan; Bessot, Nicolas; Gonidec, Julie; Zabalia, Marc; Guillois, Bernard; Roche‐Labarbe, Nadège
Abstract : Preterm infants frequently develop atypical sensory profiles, the tactile modality being particularly affected. However, there is a lack of recent investigation of neonatal tactile perception in a passive context, especially in preterms who are particularly exposed to this tactile stimuli. Our aims were to provide evidence of orienting responses (behavioral modifications directing subject's attention towards stimuli) and habituation to passive tactile stimuli in preterm neonates, to explore their ability to perceive spatial and temporal aspects of the stimulus, and to evaluate the effect of clinical factors on these abilities. We included 61 preterm neonates, born between 32 and 34 weeks of gestational age. At 35 weeks of corrected gestational age, we measured orienting responses (forearm, hand, and fingers movements) during vibrotactile stimulation of their hand and forearm; during a habituation and dishabituation paradigm, the dishabituation being either a location change or a pause in the stimulation sequence. Preterm newborns displayed a manual orienting response to vibrotactile stimuli which significantly decreased when the stimulus was repeated, regardless of the stimulated location on the limb. Habituation was delayed in subjects born at a younger gestational age, smaller birth weight, and having experienced more painful care procedures. Preterm neonates perceived changes in stimulus location and interstimulus time interval. Our findings provide insights on several aspects of the perception of repeated tactile stimuli by preterm neonates, and the first evidence of the early development of temporal processing abilities in the tactile modality. Future work will investigate the links between this ability and neurodevelopmental disorders.